2004
DOI: 10.1089/088318704322994930
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age and Administration Regimens on the Suppressive Effect of Inhaled Glucocorticoids on Eosinophil Markers in Children with Asthma

Abstract: Inhaled glucocorticoids may suppress the eosinophil markers serum eosinophil cationic protein (ECP) and urine eosinophil protein X (EPX) in children with asthma. The aim of the present study was to see whether age or administration regimen may affect the suppressive effect of inhaled budesonide on serum ECP or serum or urine EPX in children with asthma. Two separate randomized double-blind crossover trials with two treatment periods of 4 weeks duration were conducted. Study 1: Inhaled budesonide 400 mg twice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…So far, one‐time blood and spot urine collections have been mainly used in clinical studies of ECP and EPX in children. Few of the studies gave information on the time of day at which sampling was performed (42–45) and many of them may have been influenced by marked circadian variations in the measures. We have recently reported serum ECP and EPX concentrations to be considerably higher during the night than during daytime with peak levels of ECP and EPX at 06.00 hours (both markers) and trough levels at 08.00 and 12.00 hours, respectively (46).…”
Section: Methodological Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, one‐time blood and spot urine collections have been mainly used in clinical studies of ECP and EPX in children. Few of the studies gave information on the time of day at which sampling was performed (42–45) and many of them may have been influenced by marked circadian variations in the measures. We have recently reported serum ECP and EPX concentrations to be considerably higher during the night than during daytime with peak levels of ECP and EPX at 06.00 hours (both markers) and trough levels at 08.00 and 12.00 hours, respectively (46).…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…Again, conflicting results have been presented in children (15, 25, 29, 35, 42–44, 79, 81, 82). Serum ECP was suppressed in children treated with inhaled budesonide 400–600 µg (81, 82), serum ECP, serum EPX and urine EPX in children treated with 400–800 µg daily (15, 35, 45). Others have reported that serum ECP (42, 43), and serum and urine EPX (42) levels were not affected in children during treatment with inhaled fluticasone propionate 200 µg (42) or budesonide 400–800 µg per day (43) in spite of increased pulmonary function and decreased bronchial hyperreactivity.…”
Section: Monitoring Anti‐inflammatory Effects Of Inhaled Glucocorticoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood ECP concentration fell after initiation of ICS treatment and the authors suggested that ECP may be a useful marker of adherence to corticosteroid treatment [125]. However, a study by Wolthers et al [126] showed that blood ECP is not sensitive to ICS dose changes and in a study involving adults with chronic persistent asthma ICS caused a significant reduction in sputum and blood eosinophils but not sputum or blood ECP [127]. Review of the evidence suggests that sputum and blood ECP concentrations are not a sensitive or reliable means of evaluating airway inflammation.…”
Section: Serum and Sputum Ecpmentioning
confidence: 99%
“…Blood-taking was performed between 11 am to 4 pm, which is when circadian rhythm of serum ECP is fairly stable (11). Three mL of venous blood was drawn via venipuncture, collected into Serum Separating Tubes (BD Diagnostics, Belliver Industrial Estate, Plymouth, PL6 78P, UK), and allowed to clot overnight at 4 • C. They were subsequently centrifuged at 3000g at room temperature for 5 minutes.…”
Section: Serum Ecpmentioning
confidence: 99%